Experimental and DFT calculations for C/ZnO@S cathode and prelithiation Si anode for advanced sulfur-based batteries - Kiai, Maryam Sadat; Aslfattahi, Navid; Mansoor, Abdullateef; Karatas, Deniz; Baydogan, Nilgun; Samylingam, Lingenthiran; Kadirgama, Kumaran; Kok, Chee Kuang (Institute for Ionics, 2025)
The advancement of modified electrodes for the next generation of sulfur-based batteries has become a prominent focus of research. This study introduces a detailed DFT calculations for the cell with carbon-doped ZnO/S as a potential cathode material through urea-assisted thermal decomposition of zinc acetate. Ultralong cycling stability is achieved after 500 cycles at 2 C for C-doped ZnO, resulting in an impressive reversibility of 981 mAh g−1, with a capacity retention of 86.2% and minimal capacity degradation of just 0.023% per cycle. The carbon-doped ZnO/LiS2 model has a higher electrical conductivity compared to the Li2S/ZnO model. The DFT result proved the strong interaction of silicon with both carbon and oxygen; subsequently, the interaction in ZnO models containing SiS₂ was much higher, especially in the model containing carbon, which is in good agreement with our experiments.